Increasing the Quality of Blood Tofu in an Industrial Slaughterhouse of Thailand - Pussadee Tangwatcharin; Worraluk Teemeesuk; Supaluk Sorapukdee (Journal of World s Poultry Research, 2022)
Blood tofu, or cooked duck blood curd, is a Chinese delicacy in East Asia. Its quality and shelf-life are low due to microorganism contamination during production. Therefore, the present study was performed to investigate the role of sodium diacetate (SD), sodium chloride (NaCl), and polyethylene glycol 400 (PEG) combinations in increasing the quality of blood tofu. A total of 45 cooked duck blood curd samples were randomly divided into 3 groups with 3 replicates per group. The first two groups were used to investigate the effect of SD, NaCl, and PEG combinations on microbiological and physical analyses for non-inoculated samples. Another group was used to determine the effect of antimicrobial combinations on Lactobacillus plantarum, Pseudomonas fluorescens, Salmonella typhimurium, Escherichia coli, and Staphylococcus aureus in inoculated samples that were inoculated with these bacteria. All groups were treated with control-sterilized water, 0.15% SD (w/v) + 1.25% NaCl (w/v), 0.30% SD (w/v) + 1.25% NaCl (w/v), 0.15% SD (w/v) + 0.15% PEG (w/v), and 0.15% SD (w/v) + 1.25% NaCl (w/v) + 0.15% PEG (w/v). The results indicated that soaking cooked duck blood curd samples in antimicrobial agent combinations could reduce mesophile and psychrophile bacteria counts in non-inoculated samples. Additionally, 0.15% SD + 1.25% NaCl + 0.15% PEG combination had a higher reduction in mesophile and psychrophile counts, compared to soaking the samples in 0.30% SD + 1.25% NaCl, 0.15% SD + 1.25% NaCl and 0.15% SD + 0.15% PEG combinations. Similarly, this combination showed a significant decrease in lactic acid bacteria, Pseudomonas, Salmonella, Escherichia coli, and Staphylococcus aureus counts in inoculated samples. Furthermore, soaking the samples in 0.15% SD + 1.25% NaCl + 0.15% PEG combination did not negatively affect the samples’ physical quality. Soaking the samples in 0.15% SD + 1.25% NaCl + 0.15% PEG combination inhibited the growth of mesophile, psychrophile, and Pseudomonas in non-inoculated samples after storage for 10, 6, 10, and 8 days in a slaughter warehouse at 7℃, respectively, and extended shelf-life of samples for 16 days. Regarding physical quality changes, this treatment delayed the reduction of pH, hue, hardness, and chewiness of the samples after storage for 10, 8, 12, and 10 days, respectively. Thus, SD, NaCl, and PEG combination had a high preservative potential for cooked duck blood curd used in industrial slaughterhouses. Keywords: Blood curd, Duck, Organic acid salt, Polyethylene glycol, Quality changes
Keywords: Identification and Quantification in Food; Healthcare and Venom Research; Aquaculture disease management and microbiota